Clinical evaluation of enhanced recovery after surgery protocol for anterior cervical decompression and fusion (ACDF): study protocol for a multicentre randomised controlled trial - Ze Yan Liang; Chun Mei Chen; Gui Qin Zhong; Bi Hua Lin; Ren Qin Lin; Yan Juan Lin (BMJ Open)
Introduction To improve the efficacy of anterior cervical decompression and fusion (ACDF) and reduce postoperative complications in degenerative cervical myelopathy, our team established a set of perioperative care of enhanced recovery guidelines of ACDF based on the concept of enhanced recovery after surgery. In addition, a prospective, multicentre, randomised clinical trial was designed.Methods and analysis A total of 260 patients aged 18–65 years will be included. Preoperative MRI and CT will be used to confirm the typical manifestations of cervical spondylosis, such as cervical disc herniation and spinal cord compression. The patient presents with neck and shoulder pain, numbness of upper limbs, weakened grip strength and cotton sense of foot tread. Patients received normal conservative treatment for 3 months with no obvious relief or even aggravation of symptoms. Patients will be assigned to the group in strict accordance with the random allocation table. Patients in groups A and B will receive conventional perioperative care and perioperative care for enhanced recovery, respectively. The main outcome indicators are the Karnofsky Performance Scale score and the Japanese Orthopaedic Association scale. Secondary outcome indicators are pain assessment by Numeric Rating Scale, Neck Disability Index, quality of life index (QL-Index) and postoperative complications. Follow-up will be conducted at 3, 6 and 12 months postoperatively.Ethics and dissemination Ethical approval has been granted by the Ethics Committee of Fujian Medical University Union Hospital, Fuzhou, China (2020YF034-01). Results of the research will be published in an international peer-reviewed scientific journal and disseminated through presentation at scientific conferences.Trial registration number ChiCTR2000040508.